COMPARATIVE ANALYSIS OF THE PROSPECTS OF UKRAINIAN COAL MINES BY THE COPRAS-G METHOD - Zhylinska, Оksana; Balan, Valery; Petrovska, Tatiana (Ekonomika, 2013)
Abstract. The article covers the elaboration of a methodical toolkit of assessing the prospects of coal mines, which allows for the differentiation of enterprises by an integrated index of their prospects as regards mining and the geological conditions of each coal mine. Is proposed An algorithm for the coal mine prospects assessment, of containing the stages of selecting the characteristics of mining and geological conditions, the use of a multi-attribute assessment by the COPRAS-G interval data, and the rating of coal mines. A comparative analysis of the prospects, employing the COPRAS-G method, was tested on an the example of 14 coal mines of the Central district Donbass of Ukraine.Key words: comparative analysis, prospects, coal mines, multi-attribute assessment, imprecise data, COPRASG method, CEE